2013
DOI: 10.1378/chest.12-2026
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction in Children With Obstructive Sleep Apnea Is Associated With Epigenetic Changes in the eNOS Gene

Abstract: Background: Obstructive sleep apnea (OSA) is a highly prevalent disorder that has been associated with an increased risk for cardiovascular morbidity, even in children. However, not all children with OSA manifest alterations in endothelial postocclusive hyperemia, an endothelial nitric oxide synthase (eNOS)-dependent response. Since expression of the eNOS gene is regulated by epigenetic mechanisms and OSA may cause epigenetic modifi cations such as DNA hypermethylation, we hypothesized that epigenetic modifi c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 38 publications
0
59
1
1
Order By: Relevance
“…Moreover, FOXP3 DNA methylation levels not only correlated with inflammatory biomarkers and serum lipids, such as high-sensitivity C-reactive protein, myeloid-related protein-8/14 and apolipoprotein B, but were also associated with AHI and BMI z-scores [115]. The hypothesis of epigenetic modifications in children with OSA was further supported by KHEIRANDISH-GOZAL et al [116], who showed that a promoter region of the eNOS gene displayed significantly higher methylation levels in the OSA-abnormal group than the OSA-normal or control groups. This hypermethylation pattern was nicely coupled with significantly reduced eNOS mRNA expression levels in the OSA-abnormal group in comparison with the OSA-normal group, further supporting the association between DNA methylation and the OSA phenotype.…”
Section: Biomarkers In Ipf and Osamentioning
confidence: 70%
“…Moreover, FOXP3 DNA methylation levels not only correlated with inflammatory biomarkers and serum lipids, such as high-sensitivity C-reactive protein, myeloid-related protein-8/14 and apolipoprotein B, but were also associated with AHI and BMI z-scores [115]. The hypothesis of epigenetic modifications in children with OSA was further supported by KHEIRANDISH-GOZAL et al [116], who showed that a promoter region of the eNOS gene displayed significantly higher methylation levels in the OSA-abnormal group than the OSA-normal or control groups. This hypermethylation pattern was nicely coupled with significantly reduced eNOS mRNA expression levels in the OSA-abnormal group in comparison with the OSA-normal group, further supporting the association between DNA methylation and the OSA phenotype.…”
Section: Biomarkers In Ipf and Osamentioning
confidence: 70%
“…Furthermore, incremental evidence attests to vascular remodeling that progressively occurs in the context of ED since early childhood to increase CVD risk later in life (32). The degree of eNOS expression changes in naive cultured endothelial cells treated with exosomes from ED or NEF subjects markedly differed, independently from whether the exosomes originated from OB without OSA or from non-OB with OSA (22). Additionally, changes in monolayer resistance were closely associated with T max , suggesting that changes in eNOS expression and in monolayer resistance provide accurate biologic correlates of endothelial function in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The time to maximal regional blood flow after occlusion release (T max ) is representative of the postocclusion hyperemic response, an index of nitric oxide (NO)-dependent endothelial function (9,22). T max greater than 45 seconds was considered indicative of abnormal endothelial function (15 To examine the effect of exosomes on endothelial cell monolayer barrier, endothelial cells were grown to confluence into electric cell-substrate impedance sensing (ECIS) arrays as a single confluent monolayer.…”
Section: Endothelial Function Test In Childrenmentioning
confidence: 99%
“…20 Over the last decade, a constellation of morbidity-related biomarkers has been proposed for pediatric OSAS, and a scoping review was previously published and investigated potential associations and predictive abilities of such published candidate biomarkers in OSAS-induced morbidities in both adults and children. 21 In this article, we focus on the more promising of such biomarkers, and particularly on those potentially contributing to detection and monitoring of cardiometabolic morbidity (see Table 1 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] residual OSAS following T&A. 23 On the basis of the interindividual variability of the responses to T&A we previously found in a large panel of inflammatory markers among a large group of obese children with OSAS, 24 it is likely that use of CRP alone, rather than as a component of a multiarray panel, may not provide sufficiently accurate prediction of CVD risk or its resolution with treatment.…”
mentioning
confidence: 99%
“…58 30 or epigenetic changes in the promoter region of eNOS. 31 Moreover, evidence of disparate responses in endothelial progenitor cell recruitments to the circulation along with similar changes in stromal derived factor-1 plasma concentrations 68 suggests a complex interplay of coordinated cellular and gene networks contributing to the phenotypic diversity exhibited by children with OSAS. Corroborative evidence of the complexity of such pathways was uncovered through the exploration of plasma extracellular microvesicle microRNAs.…”
mentioning
confidence: 99%